SYNSEDIMENTARY TECTONICS AND SEDIMENTATION IN THE TERTIARY PIEDMONT BASIN, NORTHWESTERN ITALY - ROMANO GELATI; MARIO GNACCOLINI; MARIA ROSE PETRIZZO (Rivista Italiana di Paleontologia e Stratigrafia, 1998)
The Late Oligocene/Early Miocene tectonic and sedimentary evolution of the eastern sector of the Langhe Sub-Basin (Teriary Piedmont Basin) is proposed and discussed. The area is located between the villages of Roccaverano and Mombaldone, along the western side of the Bormida di Spigno River Valley (see attached geologic map). Synsedimentary tectonics strongly influenced the geologic evolution of the region during the time span examined, being particularly evident at three specific "times" that were chosen as models. During "Time 1" (Late Oligocene) gentle anticlines, aligned WNW-ESE and NW-SE, started to form, affecting only hemipelagic mudstones and creating structural highs that controlled the areal distribution of both turbidites (i.e.T. Ovrano High) and a thick pelitic slump sheet (i.e.M. Pisone High). During "Time 2"(Aquitanian) the C. Mazzurini Half-Graben developed, separated by W-E and WNW-ESE growth faults from the M. Ovrano High to the north and gradually connecting, through a gently sloping ramp, with the Rocchetta High to the south. Turbidity currents and debris flows were channeled into the half-graben, while hemipelagic limestones were deposited onto the adjacent higher areas. During "Time 3" (Early Burdigalian) the depocenter of the depression shifted southward, while the half-graben evolved into a wide trough (Piantivello Trough) characterized by turbidites. Subsequently, the strongly irregular topography was progressively leveled to the quite homogeneous landscape on which the Cortemilia Formation (Late Burdigalian) was deposited.